Matrix metalloproteinase (MMP)-9 in cancer-associated fibroblasts (CAFs) is suppressed by omega-3 polyunsaturated fatty acids in vitro and in vivo. - Ayumi Taguchi; Kei Kawana; Kensuke Tomio; Aki Yamashita; Yosuke Isobe; Kazunori Nagasaka; Kaori Koga; Tomoko Inoue; Haruka Nishida; Satoko Kojima; Katsuyuki Adachi; Yoko Matsumoto; et al. (PLoS ONE, 2014)
Cancer associated fibroblasts (CAFs) are responsible for tumor growth, angiogenesis, invasion, and metastasis. Matrix metalloproteinase (MMP)-9 secreted from cancer stroma populated by CAFs is a prerequisite for cancer angiogenesis and metastasis. Omega-3 polyunsaturated fatty acids (omega-3 PUFA) have been reported to have anti-tumor effects on diverse types of malignancies. Fat-1 mice, which can convert omega-6 to omega-3 PUFA independent of diet, are useful to investigate the functions of endogenous omega-3 PUFA. To examine the effect of omega-3 PUFA on tumorigenesis, TC-1 cells, a murine epithelial cell line immortalized by human papillomavirus (HPV) oncogenes, were injected subcutaneously into fat-1 or wild type mice. Tumor growth and angiogenesis of the TC-1 tumor were significantly suppressed in fat-1 compared to wild type mice. cDNA microarray of the tumors derived from fat-1 and wild type mice revealed that MMP-9 is downregulated in fat-1 mice. Immunohistochemical study demonstrated immunoreactivity for MMP-9 in the tumor stromal fibroblasts was diffusely positive in wild type whereas focal in fat-1 mice. MMP-9 was expressed in primary cultured fibroblasts isolated from fat-1 and wild type mice but was not expressed in TC-1 cells. Co-culture of fibroblasts with TC-1 cells enhanced the expression and the proteinase activity of MMP-9, although the protease activity of MMP-9 in fat-1-derived fibroblasts was lower than that in wild type fibroblasts. Our data suggests that omega-3 PUFAs suppress MMP-9 induction and tumor angiogenesis. These findings may provide insight into mechanisms by which omega-3 PUFAs exert anti-tumor effects by modulating tumor microenvironment.